Kontroversi Rencana Pemerintah dalam Menggolongkan Tarif TransJakarta ditinjau dari Aspek Hukum - wong, Sherryl naomi; Syailendra, Moody Rizqy (Jurnal Ilmiah Wahana Pendidikan, 2024)
The city of Jakarta, with its high population, extreme pollution and traffic jam problems, has made the government look for solutions to these problems. Until finally in 2004 the government discovered the BRT system which was implemented into public transportation, which was named TransJakarta. With cheap fares and wide coverage, people are starting to like using public transportation. However, recently there have been proposals related to increasing TransJakarta prices according to domicile and social status, as well as balancing electric train fares. This makes the public ask, what is the urgency underlying the proposal, and will there be an increase in service standards if the tariff is increased. The author uses a juridical-normative method to solve this problem, before finally reaching results and discussion. In the discussion, it was explained in detail the reasons why the government's urgency was not strong enough to increase tariffs. Then related to the feasibility of Minimum Service Standards which include Safety, Security, Equality and Regularity, if not implemented properly, it can become a source of legal problems involving the subject and object of transportation. Therefore, the advice that can be given is to try to take advantage of non-ticket businesses. However, if there is no other way, it would be better if the government thought about urgency or other reasons that are also beneficial for society, such as balancing price increases with increases in SPM.